Chemical Composition and Antimicrobial Assay of Essential Oil from Whole Aerial Parts of Ainsliaea aptera DC. Collected from two Different Regions of Central Himalaya. Issue 3 (4th May 2021) - Bisht, Lalit S.; Melkani, Anand B.; Prasad, Rajendra; Mohan, Lalit; Palni, Manisha; Nitwal, Leelawati
Abstract: Ainsliaea aptera DC, a medicinally important aromatic plant of the family Asteraceae grows wild in high altitude regions of Uttarakhand state (India). The essential oil samples obtained by steam distillation of its whole aerial parts collected from two different geographical regions were analyzed by GC and GC-MS. Total forty-five compounds from Tungnath sample and thirty-four compounds from Lohajung sample were identified constituting 95 % and 85.6 %, respectively of total oil composition. The terpenoid profile showed both qualitative as well as quantitative variation with respect to major constituents; E-β-farnesene (9.5 % and nil), germacrene D (14.6 % and 3.2 %), bicyclogermacrene (10.2 % and 3.3 %), δ-cadinene (4.2 % and 6.9 %), germacrene D-4-ol (nil and 4.9 %), spathulenol (11.6 % and 3.0 %), epi-α-muurolol (7.6 % and 10.8 %), α-cadinol (13.8 % and 19.5 %) and hexadecanoic acid (nil and 4.8 %). Antimicrobial activity of oil samples assayed against seven animal pathogens, three plant pathogenic bacteria, and three pathogenic fungi using the agar disc diffusion method. Both the oil samples showed moderate to very good antibacterial and antifungal potential. The oil sample from Tungnath was found to have the best activity against E. coli, Enterococcus faecalis, Staphylococcus aureus, and Salmonella enterica which was comparable to the activity shown by standard antibiotics.